Hubungan Kualitas Tidur dengan Status Fungsional Pasien Pasca Stroke Dirumah Sakit Mitra Medika Tanjung Mulia - Agus Surya Bakti; Ani Rahmadhani Kaban; Maya Ardila Siregar; Piterimasia Simanungkalit (NAJ Nursing Applied Journal, 2025)
Stroke is the world's second biggest cause of death after heart attacks. Ischemic stroke is caused by a blockage of blood vessels in the brain, resulting in a lack of oxygenated blood flow and the degeneration and death of brain tissue. This study aimed to determine the relationship between sleep quality and functional status of post-stroke patients at Mitra Medika Hospital Tanjung Mulia Medan. This is analytical survey research with cross sectional approach. The population of study was 126 respondents and the sample was determined using SPSS application obtained 56 respondents. The measurement of sleep quality used PSQI questionnaire and functional status using the Barthel index. Data analysis used pre-analysis, univariate and bivariate. The result of chi-square statistical test obtained that the P value was 0.009. Where the value was smaller than the α value of <0.05, then there was a relationship between sleep quality and functional status of post-stroke patients at Mitra Medika Hospital Medan. The results showed that 77.1% of respondents had poor sleep quality. 14.4% of respondents were in the category of moderate dependence functional status. The results of the analysis obtained a p value = 0.000 (<α=0.05) with a degree of relationship of 0.009. The study concluded that there is a significant relationship between sleep quality and functional status in post-stroke patients at Mitra Medika Hospital. It is suggested that the nursing profession increase sleep quality in post-stroke patients in order to accelerate functional status recovery.